ROLE OF THYMIDYLATE SYNTHASE REGULATION OF MYC, p53 AND OTHER GENES IN MEDIATING 5-FLUOROURACIL/LEUCOVORIN RESISTANCE IN COLORECTAL CANCER AND CF10 RESPONSE - Okechukwu, Charles Chidi (Wake Forest University, 2025)
My research explores the mechanisms underlying chemoresistance to 5-fluorouracil (5-FU)-based therapies in metastatic colorectal cancer (mCRC) and introduces CF10, a promising second-generation fluoropyrimidine (FP) polymer, as a potential treatment option. Our first paper examines the key factors contributing to 5-FU resistance, including altered anabolic metabolism, elevated thymidylate synthase (TS) expression/activity, and dysregulated programmed cell death. These resistance mechanisms can be potentially overcome with the next-generation FP polymers like CF10, which exhibit reduced dependence on anabolic metabolism and more potent TS inhibitory activity. The in-vitro and in-vivo studies demonstrate that CF10 is significantly more potent than 5-FU, causing increased apoptosis and replication stress in colorectal cancer cell lines. Importantly, CF10 dosed to deliver equivalent FP content as 5-FU did not cause weight loss, even when combined with an inhibitor of dihydropyrimidine dehydrogenase. Additionally, CF10 was more effective than 5-FU at inhibiting tumor progression in a colorectal liver metastasis (CRLM) model. Our work delves deeper into the mechanisms of acquired resistance to 5-FU/leucovorin (5-FU/LV) in mCRC cells under physiological folate conditions. It showed that 5-FU/LV resistance was associated with elevated TS levels, increased c-Myc expression, and upregulation of the Myc-target gene ABCB5, which is linked to drug resistance. Crucially, our findings revealed that the polymeric FP compound, CF10, remained highly potent against the 5-FU/LV-resistant CRC cells, effectively inducing TS ternary complex formation and inhibiting TS catalytic activity. In a clinically relevant mouse model of therapy-resistant CRC liver metastasis, CF10 and CF10/LV were highly effective, completely eradicating liver metastases and providing a significant survival advantage compared to 5-FU and 5-FU/LV. In summary, these studies provide a comprehensive understanding of the mechanisms contributing to 5-FU resistance in mCRC and present compelling preclinical evidence supporting the development of the next-generation FP polymer, CF10, as a potential treatment for 5-FU-resistant, liver-metastatic colorectal cancer.
Keywords: 5-FU/LV-resistant CRC cells; CF10 a promising second-generation fluoropyrimidine (FP) polymer; Colorectal cancer liver metastasis; metastatic colorectal cancer; Myc-target gene ABCB5; Thymidylate synthase (TS)